A Systematic Review of Dengue Fever and Dengue-Associated Neurological Conditions Was Conducted in an Attempt to Better Understand This Disease - Raúl Isea (Journal of Bioinformatics And Diabetes, 2024)
Dengue is a global arbovirus disease primarily carried by Aedes aegypti and Aedes albopictus mosquitoes. It has four serotypes (DENV1, DENV2, DENV3, and DENV4) and is classified into distinct genotypes. The epidemic is complicated by immunological interactions and viral lineage turnover. Neurological problems are commonly associated with DENV2 and DENV3, with DENV2 displaying the most severe symptoms. Direct viral invasion, host-mediated immune system reactions, or host-mediated metabolic alterations can all result in dengue-related neurological issues. The three dengue vaccinations and the significance of meta-analyses for genetic data will also be covered. Finally, establish a connection with the microRNAs associated with dengue fever, creating new opportunities for the creation of dengue treatment regimens involving microRNAs.
Keywords: Dengue fever